Physicochemical Quality and Microbial Activity of Dairy Milk with Ozonation (Jurnal Ilmu dan Teknologi Hasil Ternak, 2021)
The aim of this study was to evaluate the effect of ozone exposure to the physicochemical and microbial activity in dairy milk. The research material was fresh milk from dairy cows and ozone was produced by commercial ozone generator brand HANACO, production capacity up to 0.702 mg/min at 24-27ÂºC with oxygen source coming from ambient air in the nature. The experiment used ozone treatments for 0, 10, 20, and 30 min with variable of analysis such as density, protein, fat, electrical resistance, total plate count, and malondialdehyde which was analyzed using One Way Annova. The results showed that ozone treatment had no significant effect on the density, protein and fat in dairy milk, but had significant (P<0.05) effect on the electrical resistance, total plate count, and production of malondialdehyde. Electrical resistance and malondialdehyde were increased, while total plate count was decreased over time with the ozone exposure. Ozonation is possible to reducing yield loss on milk production that is caused by microbial activity without changing the physicochemical properties of dairy milk.